Prove the identities secx – secx = tanx + tanx

Asked by Aaryan | 1 year ago |  89

##### Solution :-

Let us consider LHS: secx – secx

(secx)2 – secx

By using the formula, sec2 θ = 1 + tan2 θ.

(1 + tanx)2 – (1 + tanx)

1 + 2tanx + tanx – 1 – tanx

tanx + tanx

= RHS

LHS = RHS

Hence proved.

Answered by Sakshi | 1 year ago

### Related Questions

#### prove that sin 8π/3 cos 23π/6 + cos 13π/3 sin 35π/6 = 1/2

prove that $$sin \dfrac{8π}{3} cos \dfrac{23π}{6} + cos \dfrac{13π}{3} sin \dfrac{35π}{6} = \dfrac{1}{2}$$

#### prove that 3 sin π/6 sec π/3 – 4 sin 5π/6 cot π/4 = 1

prove that $$3 sin \dfrac{π}{6} sec \dfrac{π}{3} – 4 sin \dfrac{5π}{6} cot \dfrac{π}{4} = 1$$

#### prove that tan 11π/3 – 2 sin 4π/6 – 3/4 cosec2 π/4 + 4 cos2 17π/6 = (3 – 4\sqrt{3})/2

prove that $$tan \dfrac{11π}{3} – 2 sin \dfrac{4π}{6} – \dfrac{3}{4} cosec^2 \dfrac{π}{4} + 4 cos^2 \dfrac{17π}{6} = \dfrac{(3 – 4\sqrt{3})}{2}$$

#### prove that cos 570° sin 510° + sin (-330°) cos (-390°) = 0

prove that cos 570° sin 510° + sin (-330°) cos (-390°) = 0

#### prove that tan (-125°) cot (-405°) – tan (-765°) cot (675°) = 0

prove that tan (-125°) cot (-405°) – tan (-765°) cot (675°) = 0